2007
DOI: 10.1158/0008-5472.can-07-0722
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tumor Necrosis Factor-α and TRAIL in High-Dose Radiation–Induced Bystander Signaling in Lung Adenocarcinoma

Abstract: In the present study, ionizing radiation (IR)-induced bystander effects were investigated in two lung cancer cell lines. A549 cells were found to be more resistant to radiation-conditioned medium (RCM) obtained from A549 cells when compared with the H460 exposed to RCM procured from H460 cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 48 publications
4
80
0
Order By: Relevance
“…In tumor cell lines and tumors representing prostate, kidney and gastric cancer, EGR1 stimulated tumor cell growth and was associated with a poor prognosis (15,16). By contrast, in fibrosarcoma, glioblastoma, melanoma and esophageal lung and breast cancer, EGR1 is reported to be a tumor suppressor (7,8,(17)(18)(19)(20). Of the head and neck cancers, only in nasopharyngeal carcinoma was it found that the expression of EGR1 had a positive prognostic effect on survival (21).…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cell lines and tumors representing prostate, kidney and gastric cancer, EGR1 stimulated tumor cell growth and was associated with a poor prognosis (15,16). By contrast, in fibrosarcoma, glioblastoma, melanoma and esophageal lung and breast cancer, EGR1 is reported to be a tumor suppressor (7,8,(17)(18)(19)(20). Of the head and neck cancers, only in nasopharyngeal carcinoma was it found that the expression of EGR1 had a positive prognostic effect on survival (21).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation assay was described earlier (Shareef et al, 2007) using 2-5 Â 10 9 PC3 cells. PCR was performed using specific primers for BAX promoter (5 0 -GC CTGGGCAACACAGTGAG-3 0 and 5 0 -GCTCCCTCGGGA GGTTTG-3 0 ) that yielded B500 bp product.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…Bystander signals may be transferred to surrounding cells either by gap junctional intercellular communication or by the production of soluble extracellular factors released from irradiated cells. Soluble signaling factors such as reactive oxygen species (ROS) (8)(9)(10)(11)(12), nitric oxide (NO) (12)(13)(14), secondary messengers like calcium (4,(8)(9)(10), cytokines such as interleukins (15)(16)(17), TGFb (18,19), TNFa and TRAIL (20,21) have been found to play a major role in radiation-induced bystander effects. A new mechanism for communication by soluble factors could be by intercellular communication by exosomes.…”
Section: Introductionmentioning
confidence: 99%